1/3+(5/12)x-2=6(2/3)

Simple and best practice solution for 1/3+(5/12)x-2=6(2/3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/3+(5/12)x-2=6(2/3) equation:



1/3+(5/12)x-2=6(2/3)
We move all terms to the left:
1/3+(5/12)x-2-(6(2/3))=0
Domain of the equation: 12)x!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
(+5/12)x-2+1/3-(6(+2/3))=0
We multiply parentheses
5x^2-2+1/3-(6(+2/3))=0
We calculate fractions
5x^2-2=0
a = 5; b = 0; c = -2;
Δ = b2-4ac
Δ = 02-4·5·(-2)
Δ = 40
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{40}=\sqrt{4*10}=\sqrt{4}*\sqrt{10}=2\sqrt{10}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{10}}{2*5}=\frac{0-2\sqrt{10}}{10} =-\frac{2\sqrt{10}}{10} =-\frac{\sqrt{10}}{5} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{10}}{2*5}=\frac{0+2\sqrt{10}}{10} =\frac{2\sqrt{10}}{10} =\frac{\sqrt{10}}{5} $

See similar equations:

| (7x+14)+(3x+36)=180 | | 3-5x/4=3x-2 | | 15+3x=3(2−2x) | | 3(2/3x-4)=x-9 | | 2+4m=-30 | | 2(-x-3)=1/2(8x+12) | | 2/3(15-6x)=-1/2(4x-10) | | 2m-2=9-m-6 | | B9x)=40.75-0.06x | | -5+p=-16 | | 6.3z=-69.3 | | -3-2c=7+10-7c | | -(7-4x)=-5x-(-8) | | 6=y/192 | | -1=(-8n+3.9) | | x-2+2x=5+3x-7 | | 34+w/2=-11 | | 25+7x=-17 | | 2p-4=2(p+1) | | c+7=9-5c | | k^2-2k-63=0 | | 14x+2=9x−39x−3 | | 16+1-8h-h=-5-3 | | 6(5x-6)=-6 | | 3(3x-2)=2(x+4) | | 180=-9x | | n=3n-27 | | 8/x–10=10+20 | | y+2.3=2.5 | | 4(-4+7x)=-100 | | 9+2y=1+6y | | V(a)=(8+-2×)(6+-2×)(a) |

Equations solver categories